On collective improvisation in crisis management – A scoping study analysis. (December 2018) - Frykmer, Tove; Uhr, Christian; Tehler, Henrik
Highlights: Existing research on collective improvisation not sufficiently described. Individual improvisation is oftentimes simply aggregated to a collective level. Methods on measuring improvisation need more precision and transparency. More research is needed on collective improvisation and performance. Abstract: Responding to crises requires the ability to meet the unforeseen and adapt to new conditions. The transboundary nature of crises with e.g. increased interconnectedness among critical infrastructures, involving more actors in response, will call for collective coordination. Collective improvisation can be a tool for handling challenges under these circumstances, however the research is limited and dispersed over disciplines. Therefore, the aim of this paper is to explore the capability to improvise collectively in crisis management, and how it affects performance. To achieve this, we conducted a structured scoping study of improvisation in scientific literature and found that existing research is not sufficiently explained or detailed to fulfill our purpose. Our findings show that individual improvisation seems to be aggregated to a collective level without modifications, and existing methods lack in precision and transparency. Further, there is a need for a more nuanced discussion on improvisation and performance. Implications are that studies on collective improvisation risk measuring individual rather than collective improvisation, if based on existing literature. Moreover, the concept of improvisation is connected to mostly positive outcomes and assumed to have the same meaning for everyone. As a result, one should be careful when using the concept in practice, e.g. when using it as a causal explanation for successful performance, or when suggesting measures aimed at improving the capability to improvise collectively. To move forward, we suggest adopting collective problem solving as a broader analytical frame. Finally, we highlight some theories serving as a starting point for this investigation.